EV01: a phase I trial in healthy HIV negative volunteers to evaluate a clade C HIV vaccine, NYVAC-C undertaken by the EuroVacc Consortium. - Bart, P; Goodall, R; Barber, T; Harari, A; Guimaraes-Walker, A; Khonkarly, M; Sheppard, N; Bangala, Y; Frachette, M; Wagner, R; Liljeström, P; Kraehenbuhl, J; et al. (2008)
NYVAC-C (vP2010), a recombinant vector expressing HIV subtype C gag, pol, env and nef antigens, was tested in a phase I study in healthy, HIV negative volunteers in London and Lausanne. Twenty-four participants were randomised to receive NYVAC-C (20) or matching placebo (4) at weeks 0 and 4, and assessed for safety and immunogenicity over 48 weeks. There were no serious adverse events, and no clinical or laboratory abnormalities or other events that led to withdrawal, interruption or dose reduction of the NYVAC-C/placebo. Half of the 10 assessed responded in the ELISpot assay under stringent criteria, which informed the sample size for a DNA-NYVAC-C comparison to NYVAC-C alone.